Nicholas Reactions of Pentadiynyl–Co2(CO)6 Cations. Synthesis of Antimalarial Hinokiresinol Analogues - Muresan, Marcus; Green, James R. (Synthesis, 2024)
Penta-1,4-diyn-3-ol–Co2(CO)6 complexes undergo Lewis acid mediated Nicholas reactions with high selectivity at the C-3 site, to give skipped (1,4-)diyne complexes. The compatible nucleophiles have a wide range of reactivity. The methodology has been applied to the synthesis of both (E)- and (Z)-isomers of a hinokiresinol and nyasol analogue, the (E)-isomer of which is known to have elevated antiplasmodial and antimalarial activity.
Keywords: propargyl; carbocations; alkyne complexes; diynes; Lewis acids; norneolignans; antimalarial agents